Teaching Bacterial Arrangements and Morphologies with Candy - Lisa Ann Blankinship (American Society for Microbiology, 2011)
Determining bacterial morphology and arrangement is a first lesson in undergraduate microbiology or in an introductory lecture to the Prokaryotes in general biology. By identifying cell arrangement and morphology, students can successfully communicate descriptives in microscopy-based labs, can take the first steps in identifying unknown organisms, and are able to understand genus and/or species names of standard laboratory bacteria. This activity is intended to help students visualize and practice naming basic bacterial morphology and arrangements, and is appropriate in either the laboratory or lecture setting of a general microbiology or introductory biology course. Students with a weak background and non-science majors will benefit most from this activity.